Seasonal variation and spatial transport of polycyclic aromatic hydrocarbons in water of the subtropical Jiulong River watershed and estuary, Southeast China - Wu, Yuling; Wang, Xinhong; Ya, Miaolei; Li, Yongyu; Hong, Huasheng (Chemosphere (Oxford), 2019)
Riverine runoff is one of the most important pathways of pollutants entering the oceans. To study the seasonal variations, spatial transports, sources and mass fluxes of polycyclic aromatic hydrocarbons (PAHs) from the subtropical Jiulong River watershed to estuary, water samples were collected in wet and dry seasons. PAH concentrations showed significant temporal-spatial variations (ANOVA, p < 0.05). In the watershed, PAH concentrations in wet season (48.6 ± 18.2 ng L−1) were significantly lower than in dry season (90.3 ± 18.5 ng L−1). In contrast, estuarine PAH concentrations in wet season (67.1 ± 24.6 ng L−1) were significantly higher than in dry season (27.4 ± 10.6 ng L−1) (p < 0.0001). The spatial variations of PAH concentrations in wet and dry seasons reflected positive and restricted transport processes occurred in the river. These findings might be subjected to seasonal changes in precipitation, water discharge, hydrodynamic conditions, and human activities. The compositional patterns of PAHs illustrated that fluorene and phenanthrene were the dominant compounds in the watershed, while phenanthrene was predominant in the estuary. Source analysis by molecular diagnostic ratios and PMF model indicated that fossil fuel and biomass combustion and petroleum both contributed to the presence of PAHs, and the high contributions of pyrogenic PAHs might be related to urban rainstorm runoff in winter and atmospheric inputs in winter. Although the estimated flux of PAHs from watershed to estuary was about 676 kg yr−1 with a low level by comparing the data obtained in the worldwide, continue concern of PAHs in the Jiulong River is recommended due to the intense human activities. •PAH concentrations displayed significant temporal and spatial variations.•Compositional patterns of PAHs were different between watershed and estuary.•Combustion and petroleum both contributed to the presence of PAHs.•Fluvial transport of riverine PAHs was dominate in summer than in winter.•Flux of riverine PAHs transported to the estuary was at a low level globally.